Ferreting out Tunneling: An Application to Indian Business Groups - Bertrand, M.; Mehta, P.; Mullainathan, S. (Quarterly Journal of Economics, 2002)
Owners of business groups are often accused of expropriating minority shareholders by tunneling resources from firms where they have low cash flow rights to firms where they have high cash flow rights. In this paper we propose a general methodology to measure the extent of tunneling activities. The methodology rests on isolating and then testing the distinctive implications of the tunneling hypothesis for the propagation of earnings shocks across firms within a group. When we apply our methodology to data on Indian business groups, we find a significant amount of tunneling, much of it occurring via nonoperating components of profit.